Standard of Crushing Value of Coarse Aggregates for Permeable Asphalt Mixture Based on Contact Stress between Aggregates - Tian Xiaoge; Wang Xiaofei; Yuan Huitong (Journal of Engineering)
Crushing resistance of coarse aggregate is the key to the stability and durability of the skeleton structure of permeable asphalt (PA) mixture. To determine the technical requirements of crushing value of coarse aggregate used in PA mixture, step-loading compression tests were conducted on the mixtures of PA-13 and a control asphalt mixture AC-13, respectively. Virtual compression tests under the same loading conditions were simulated on the corresponding digital specimens with PFC2D®. By comparing the load-deformation curves obtained from the actual tests and virtual simulation, the values of the microscopic parameters of the two graded mixtures were obtained through trial calculation and adjustment. Then, the states of contact stress between aggregates in PA-13 and AC-13 mixtures under the standard crushing pressure (400 kN) were analyzed with PFC2D®. It was found that the average normal contact stress and the maximum normal contact stress between aggregates in PA-13 were 1.71 times and 1.28 times larger than those in AC-13, respectively. The crushing values of two different lithologic coarse aggregates were measured under different pressures, 400 kN or 600 kN, respectively. The crushing value criterion of coarse aggregates used in the PA mixture was suggested to be no greater than 16% after comparative analysis.